Effects of Peritoneal Fluid on Sperm Motility and Viability in Endometriosis - Tasya, Marissa (Indonesian Journal of Obstetrics and Gynecology, 2011)
Objective: To know the effects of peritoneal fluid on sperm motility and viability in patients with endometriosis. Design/data identification: This was a laboratory experimental study to peritoneal fluid from endometriosis and non-endometriosis patients who underwent surgery in Dr. Hasan Sadikin Hospital and around with endoscopy facility which fulfill inclusion and exclusion criterias. Experiments was performed in ASTER Fertility Clinic, Dr. Hasan Sadikin Hospital. Method: Semen samples were normozoospermic of which has been prepared using swim up method with sperm count 3 x 106/ml. The sperm were exposed to peritoneal fluid from endometriosis and non-endometriosis patients and analyzed at h 0, 1, 3, 6, and 24 to see the difference of sperm motility and viability postincubation with endometriosis peritoneal fluid. The sperm viability was detected using trypan blue 0.4%. Result: Exposure of sperm to peritoneal fluid reduced sperm motility significantly from the h 6 observation (Zw = 2.17; p = 0.03) and the h 24 (Zw = 2.35; p = 0.01). The sperm viability which incubated with endometriosis peritoneal fluid reduced significantly from h 6 observation (Zw = 1.99; p = 0.04) and the h 24 (Zw = 2.55; p = 0.01). Conclusion: The endometriosis peritoneal fluid reduced the motility and viability of the sperm began from the h 6 postincubation. This indicate the possibility of involvement of endometriosis peritoneal fluid to infertility. [Indones J Obstet Gynecol 2011; 35-1: 18-20] Keywords: sperm motility, sperm viability, endometriosis